Pseudoachondroplasia: Phenotype and genotype in 11 Indian patients. Issue 3 (9th November 2021) - Jacob, Prince; Bhavani, Gandham Sri Lakshmi; Shah, Hitesh; Galada, Chelna; Nampoothiri, Sheela; Kamath, Nutan; Phadke, Shubha R.; Muranjan, Mamta; Datar, Chaitanya A.; Shukla, Anju; Girisha, Katta M.
Abstract: Pseudoachondroplasia (PSACH) is an autosomal dominant disorder characterized by rhizomelic short‐limbed skeletal dysplasia. The primary clinical and radiographic features include disproportionate dwarfism, joint laxity and hyperextensibility, exaggerated lumbar lordosis, and late ossification of the epiphyses. Identification of disease‐causing variants in heterozygous state in COMP establishes the molecular diagnosis of PSACH. We examined 11 families with clinical features suggestive of PSACH. In nine families, we used Sanger sequencing of exons 8–19 of COMP (NM_000095.2) and in two families exome sequencing was used for confirming the diagnosis. We identified 10 de novo variants, including five known variants (c.925G>A, c.976G>A, c.1201G>T, c.1417_1419del, and c.1511G>A) and five variants (c.874T>C, c.1201G>C, c.1309G>A, c.1416_1421delCGACAA, and c.1445A>T) which are not reported outside Indian ethnicity. We hereby report the largest series of individuals with molecular diagnosis of PSACH from India and reiterate the well‐known genotype–phenotype corelation in PSACH.